Determinan Omzet Merchant QRIS di Kabupaten Manokwari Sebelum dan Saat Pandemi COVID-19 - Djofar, Rizka F; Rahayu, Yuyun Puji; Tewernusa, Ketysia Imelda (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2024)
The purpose of this study is to analyze the factors that influence the revenue of QRIS Merchant s in Manokwari Regency. The data analysis technique used in this study is multiple linear regression. The primary data used was collected from 30 MSME respondents. The results of this study indicate that the period of use of QRIS, types of goods, and revenue conditions before and during the COVID-19 pandemic have a very significant effect on revenue simultaneously and partially at a confidence level of 95%. In addition, it is known that the coefficient of determination (Adjusted R Square) obtained is 0.962. This means that 96.2% of the revenue, can be explained by the period of use of QRIS, types of goods, and revenue conditions before and during the COVID-19 pandemic, while the remaining 3.8% is explained by other variables outside this study.